Intermediate Algebra

Factor by grouping, if possible, and check
5x3 + 4x2 − 10x – 8

1. 👍 0
2. 👎 0
3. 👁 111
1. try 5 x^3 - 10 x and 4 x^2 - 8
5 x(x^2-2) and 4(x^2-2) ah ha
(x^2-2)(5x+4)

1. 👍 0
2. 👎 0

Similar Questions

1. math

Consider the polynomial p(x)=32x5y−2xy5. Part A: What is the complete factorization of p(x)=32x5y−2xy5 over the integers? Part B: What methods are used to factor p(x)=32x^5y−2xy^5? Select one answer for Part A and select all

asked by Ace on December 6, 2019

1. What is the degree of the monomial 3x2y3? 2 3 5 6 2. What is the simplified form of 8b3c2 + 4b3c2? 12bc 12b3c2 12b6c4 12b9c4 3. What is the simplified form of (4j2 + 6) + (2j2 – 3) ? (1 point) (0) 6j2 – 3 (1) 6j2 + 3 (0)

asked by Deborah on January 28, 2013
3. precal

factor by grouping 5x^3-x^2-45x-9=0

asked by jill on January 26, 2020
4. Algebra

1. What polynomial has a graph that passes through the given points? (-2, 2) (-1, -1) (1, 5) (3, 67) A. y = -x3 + 4x2 + 2x - 2 B. y = x3 + 4x2 + 2x - 2 C. y = x4 + 4x3 + 2x2 - 2x D. y = x3 - 4x2 - 2x - 2 B? 2. Write -2x 2(-5x 2

asked by Ciaria on March 16, 2015
5. Algebra

Factor by grouping: 2x^2 - 4x + x - 2

asked by Michelle Summer on January 18, 2013
1. Math

Can someone please check my answers below for accurateness? The instructions are: Differentiate and simplify. 1) y=(2x^2+3x-1)(3x^2-5x-3) y'=(4x+3)(3x^2-5x-3)+(2x^2+3x-1)(6x-5) 2) y=(5x^2+3x-1)(3x^2-5x-3)

asked by Christine on August 7, 2009
2. Linear Algebra

Use Gauss Jordan Elimination to write the solution of the system of equations: x1+4x2+2x3=17 3x1+x2-5x3=7 2x1-3x2-7x3=-10

asked by Sharon on March 15, 2014
3. PreCalc

x² + 10x + 25 – 9y² I am asked to state if this polynomial is prime or to factor it. I can clearly see that you can take the SQRT of the equation, however, there is a 10x there that is not a perfect square. What am I doing

asked by Art on October 30, 2018
4. algebra 2

Factor x3 4x2 3x + 18 = 0, given that 3 is a zero.

asked by Zac on January 10, 2011
5. Algebra

almost done with Algebra...help! 2 3x – 6(2x – 0.055) = 10x + 0.515 I don't know what want but assuming your solving for x... 23x-12x-.33= 10x + 0.515 11x-.33= 10x + 0.515 x= 0.845 You need to clarify your post. Is that 23x or

asked by Mathew on August 16, 2007
6. Math Algebra 1

i was wondering if anyone could help me on this problem. expand: x^-2 (y^2 + 10x) z^3 (5x + 3z^-4) First one: x^-2 (y^2 + 10x) x^-2 is the same thing as 1/x^2. Therefore, we have this: 1/x^2 (y^2 + 10x) Multiply using the

asked by cassii on August 8, 2006